Head first PHP & MySQL - Beighley, Lynn (O'Reilly Media, Inc., 2009)
If you're ready to create web pages more complex than those you can build with HTML and CSS, Head First PHP & MySQL is the ultimate learning guide to building dynamic, database-driven websites using PHP and MySQL. Packed with real-world examples, this book teaches you all the essentials of server-side programming, from the fundamentals of PHP and MySQL coding to advanced topics such as form validation, session IDs, cookies, database queries and joins, file I/O operations, content management, and more. Head First PHP & MySQL offers the same visually rich format that's turned every title in the Head First series into a bestseller, with plenty of exercises, quizzes, puzzles, and other interactive features to help you retain what you've learned. Use PHP to transform static HTML pages into dynamic web sites Create and populate your own MySQL database tables, and work with data stored in files Perform sophisticated MySQL queries with joins, and refine your results with LIMIT and ORDER BY Use cookies and sessions to track visitors' login information and personalize the site for users Protect your data from SQL injection attacks Use regular expressions to validate information on forms Dynamically display text based on session info and create images on the fly Pull syndicated data from other sites using PHP and XML Throughout the book, you'll build sophisticated examples -- including a mailing list, a job board, and an online dating site -- to help you learn how to harness the power of PHP and MySQL in a variety of contexts. If you're ready to build a truly dynamic website, Head First PHP & MySQL is the ideal way to get going.
Print version record
Keywords: MySQL (Electronic resource); PHP (Computer program language); Web site development; PHP (Langage de programmation); Sites Web; Développement